Development of enterprises innovative activity in Kazakhstan: analysis of patenting - Mamrayeva, D.G.; Toxambayeva, A.B.; Tashenova, L.V. (BUKETOV BUSINESS REVIEW, 2021)
Object: To investigate the state of enterprises innovation activity of the Republic of Kazakhstan. Methods: The general scientific methods, methods of analysis, comparison and systematization have been used. Results: Modern trends in the development of enterprises innovative activities of the Republic of Kazakhstan in particular, quantitative values of the market innovative products in Kazakhstan for 2009–2020 were analyzed. Statistical data on the main indicators of enterprises innovation activity and the dynamics of internal research costs were presented and examined. The features and differences of innovation activity by regions of the country were revealed. The analysis of a number of submitted applications and issued patents for inventions, industrial designs, utility models was carried out. The dynamics of patent activity of national and foreign applicants were shown. Conclusions: Industrial property market of the Republic of Kazakhstan has undergone significant changes during the analyzed period, along with this, there is a positive dynamic of its development. Even though the process of commercialization of intellectual property in the country is not yet sufficiently developed, a stable innovative activity is characterized for most regions of Kazakhstan. The positive dynamics of the licensed trade development in industrial property objects have been revealed, while the predominant number of patents for inventions, industrial designs and utility models belongs to domestic innovators.